Brexit and multilingualism in the European Union. (22nd January 2022) - Ginsburgh, Victor; Moreno‐Ternero, Juan D.
Abstract: The European Union (EU) spends more than one billion euros per year ensuring translation and interpretation of 24 languages to preserve multilingualism. We examine how this budget should be fairly allocated, taking into account linguistic and economic realities of each member country. Our analysis tries to estimate the value of keeping English as a procedural language (in fact, almost a lingua franca ) in the post‐Brexit EU, where, today, just about one percent of the population speaks it as native language.